2010
DOI: 10.1053/j.gastro.2010.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 Promotes Steatohepatitis by Induction of Interleukin-1β in Mice

Abstract: BACKGROUND & AIMS Development of nonalcoholic steatohepatitis (NASH) involves the innate immune system and is mediated by Kupffer cells and hepatic stellate cells (HSCs). Toll-like receptor 9 (TLR9) is a pattern recognition receptor that recognizes bacteria-derived cytosine phosphate guanine (CpG)–containing DNA and activates innate immunity. We investigated the role of TLR9 signaling and the inflammatory cytokine interleukin-1β (IL-1β) in steatohepatitis, fibrosis, and insulin resistance. METHODS Wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
669
4
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 671 publications
(711 citation statements)
references
References 52 publications
29
669
4
9
Order By: Relevance
“…However, similar to what reported for ASH, also in experimental NASH and in human NASH patients a clear increase in LPS levels has been detected, which is likely to be due to intestinal bypass [122]. Although the role of fatty acids in activating TLRs is still controversial, although described, interesting studies on transgenic mice have shown that the absence of either TLR4 or TLR9 results in a significant reduction of NASH related parameters like histological score, hepatocyte death (apoptosis and necrosis) and markers of fibrogenesis [123][124][125]. These studies pointed out that TLR9 seems to be relevant for significant IL-1β production from Kupffer cells in experimental NASH not only in relation to steatosis but also in relation to HSC activation and hepatocyte death.…”
Section: Inflammasomes and Liver Fibrogenesismentioning
confidence: 97%
See 2 more Smart Citations
“…However, similar to what reported for ASH, also in experimental NASH and in human NASH patients a clear increase in LPS levels has been detected, which is likely to be due to intestinal bypass [122]. Although the role of fatty acids in activating TLRs is still controversial, although described, interesting studies on transgenic mice have shown that the absence of either TLR4 or TLR9 results in a significant reduction of NASH related parameters like histological score, hepatocyte death (apoptosis and necrosis) and markers of fibrogenesis [123][124][125]. These studies pointed out that TLR9 seems to be relevant for significant IL-1β production from Kupffer cells in experimental NASH not only in relation to steatosis but also in relation to HSC activation and hepatocyte death.…”
Section: Inflammasomes and Liver Fibrogenesismentioning
confidence: 97%
“…Of interest, IL-1β induced fibrogenic responses in HSCs, including secretion of tissue inhibitor of metalloproteinase-1 whereas IL-1R(-/-) mice had reduced steatohepatitis and fibrosis, compared with WT mice. Mice deficient in MyD88, an adaptor molecule for TLR9 and IL-1R signaling, also had reduced steatohepatitis and fibrosis [123].…”
Section: Inflammasomes and Liver Fibrogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Although a direct contribution of TLR9 and inflammasome activation to COPD pathogenesis is still unclear, 37,38 IL1B/interleukin 1b, a representative senescence-associated secretory phenotype (SASP) factor involved in COPD development, 39,40 is produced and activated through TLR9 signaling and inflammasome machinery. 41,42 Accordingly, insufficient mitophagy-mediated cell autonomous activation of TLR9 and the inflammasome may partly explain persistent inflammation after smoking cessation, which may also be associated with inflammation-mediated acceleration of cell senescence during COPD progression. 43 However, we understand the potential limitations of our in vitro experimental models using short-term CSE exposure to elucidate the mechanisms for COPD development.…”
Section: Wwwtandfonlinecommentioning
confidence: 99%
“…Activation of inflammasomes in immune cells is required in a range of tissue injury and repair, including alcoholic and nonalcoholic hepatitis and liver fibrosis (7,11,16,23,34). The minimum activation requirements for the inflammasome machinery have been identified and consist of two signals.…”
mentioning
confidence: 99%